Competency Disparities: Dissecting the English Proficiency Mapping across Southeast Asia - Nelya Juita; Ressy Novasary (English Education Program, Education Faculty, Universitas Nurul Huda, 2026)
This study aims to map the English proficiency index across ASEAN member countries and analyze the structural factors causing competency gaps between 2021 and 2025. Employing a descriptive-comparative method with a literature review approach, this study analyzes secondary data from the EF English Proficiency Index (EF EPI) of eight Southeast Asian countries selected via purposive sampling. The results demonstrate a sharp macroeconomic polarization in linguistic competency. Malaysia and Philippines secure the top tier within the